Infrared photodissociation spectroscopic studies of ScO(H2O)n=1–3Ar+ cluster cations: solvation induced reaction of ScO+ and water. Issue 28 (3rd July 2019) - Chen, Yinjuan; Jin, Jiaye; Xin, Ke; Yu, Wenjie; Xing, Xiaopeng; Wang, Xuefeng; Wang, Guanjun
Abstract : We investigate the gaseous ScO(H2 O)1–3 Ar + cations prepared by laser vaporization coupled with supersonic molecular beam using infrared photodissociation spectroscopy in the O–H stretching region. Abstract : We investigate the gaseous ScO(H2 O)1–3 Ar + cations prepared by laser vaporization coupled with supersonic molecular beam using infrared photodissociation spectroscopy in the O–H stretching region. The cation structures are characterized by comparing the experimentally observed frequencies with the simulated vibration spectra. We reveal that stoichiometric ScO(H2 O)Ar + is intrinsically the hydrated oxide cation expressed as H2 O–ScOAr + hydrate rather than Sc(OH)2 Ar + dihydroxide, although the former is higher in energy by 29.5 kcal mol −1 than the latter. Interestingly, when more water molecules are introduced to the complex, we find that the stoichiometric ScO(H2 O)2–3 Ar + embraces the core subunit of Sc(OH)2 + . Theoretical calculations suggest that the energy barrier of hydrogen transfer plays a critical role in the isomerization from hydrated complex to dihydroxide. When more than one water molecule is involved in the complex, the hydrogen transfer becomes nearly barrierless through a six-member cyclic transition state, leading to the reduction in the energy barrier from 21.8 kcal mol −1 to 4.2 kcal mol −1 . Altogether, we conclude that the solvent molecules such as water can decrease the energy barrier and thus induce the formation of hydroxy species in the hydrolysis process.